2018
DOI: 10.1200/jco.2017.77.0388
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor Activity of Nivolumab in Recurrent and Metastatic Nasopharyngeal Carcinoma: An International, Multicenter Study of the Mayo Clinic Phase 2 Consortium (NCI-9742)

Abstract: Purpose This multinational study evaluated the antitumor activity of nivolumab in nasopharyngeal carcinoma (NPC). Tumor and plasma-based biomarkers were investigated in an exploratory analysis. Patients and Methods Patients with multiply pretreated recurrent or metastatic NPC were treated with nivolumab until disease progression. The primary end point was objective response rate (ORR) and secondary end points included survival and toxicity. The expression of programmed death-ligand 1 (PD-L1) and human leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
376
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 347 publications
(387 citation statements)
references
References 34 publications
8
376
3
Order By: Relevance
“…The study authors suggested a higher proportion of patients received three or more prior chemotherapy regimens than equivalent trials investigating R/M NPC. As per Table , their proportion is comparable to the nivolumab NCI‐9742 trial, but slightly higher than the camrelizumab monotherapy trial …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study authors suggested a higher proportion of patients received three or more prior chemotherapy regimens than equivalent trials investigating R/M NPC. As per Table , their proportion is comparable to the nivolumab NCI‐9742 trial, but slightly higher than the camrelizumab monotherapy trial …”
Section: Resultsmentioning
confidence: 99%
“…( a ) Overall progression‐free survival (PFS) analysis for all four studies. Fang Combination Camrelizumab (Top L), Fang Monotherapy Camrelizumab (Top R), Ma Nivolumab (Bottom L), Hsu Pembrolizumab (Bottom R) . ( b ) Overall PFS based on the two studies with similar inclusion criteria and study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations